Argentina : Second Review under the Stand-By Arrangement; Financing Assurances Review; and Request for Modification of Performance Criterion-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
The redesigned IMF-supported economic reform program is bearing early results. Financial markets have stabilized since end-September, following the adoption of the new monetary policy framework. After the appreciation of the currency in October, the peso has floated within the non-intervention zone. Short-term interest rates have fallen back to their end-September level. The passage of the 2019 Budget with broad political support has helped solidify confidence in the authorities' stabilization plan. As a result, demand for Argentine bonds has strengthened and sovereign risk premia have narrowed.